Apparent Reaction Kinetics of Crude Palm Oil Dechlorination Using Sodium Silicate Solution - Zulfa Kurnia Umani Hari; Nur Shafikah Rasad; Mohd Sabri Mahmud (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
This paper reports a study of the apparent reaction kinetics of crude palm oil (CPO) dechlorination using a sodium silicate (SS) solution, providing a water-efficient alternative to conventional washing to mitigate the 3-MCPD precursor. Three CPO-to-SS volume ratios (0.25, 2.33, and 3.00) were tested across temperatures of 60 °C, 70 °C, and 80 °C. The results showed the 2.33 ratio as most effective, achieving 1000 times of extraction, as indicated by the McCabe-Thiele equilibrium plot. Kinetic analysis revealed a transition from pseudo-first-order regimes at lower temperatures to exceptionally high apparent reaction orders (up to 24.90) at 80 °C. These high orders indicate a mass-transfer limited process where declining SS concentration might have destabilized the emulsion, making the reaction rate sensitive to interfacial surface area. The FTIR spectra confirmed that SS acted as both a buffering agent and a dispersant, reducing moisture retention without clear free fatty acid neutralization. The elevated temperatures significantly enhanced dechlorination rates, with the 0.25 ratio facilitating chloride breakdown with the highest rate constant. The results revealed that the kinetic rate is: with the rate constant, k (range 3.6 × 10-3 until 1×10 -111) and the apparent order, (range up to 24.9) at 80 ºC. These findings conclude that SS can effectively reduce chlorine content in CPO, and that process is strongly governed by the phase volume ratio and operating temperature. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).